2017
DOI: 10.1002/lary.26943
|View full text |Cite
|
Sign up to set email alerts
|

Toolbox of assessment tools of technical skills in otolaryngology–head and neck surgery: A systematic review

Abstract: Our study reports on published tools for assessing technical skills for OTL-HNS residents during core procedures conducted in the OR. These assessment tools could facilitate the provision of timely feedback to trainees including specific goals for improvement. However, the paucity of publications suggests little agreement on how to best perform work-based direct-observation assessment for core surgical procedures in OTL-HNS. The sparsity of tools specific to OTL-HNS may become a barrier to a fluid transition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…We performed a secondary analysis of data generated through a systematic review conducted by our group in 2016. As reported in the initial study, we searched for all OTL–HNS assessment tools evaluating technical skills of residents in the operating room (OR). The complete review methodology, as well as the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses diagram, is detailed in the initial study …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We performed a secondary analysis of data generated through a systematic review conducted by our group in 2016. As reported in the initial study, we searched for all OTL–HNS assessment tools evaluating technical skills of residents in the operating room (OR). The complete review methodology, as well as the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses diagram, is detailed in the initial study …”
Section: Methodsmentioning
confidence: 99%
“…For this secondary analysis, we included all 16 articles from the previous review and focused on validity evidence reported in each article. Data extraction included sample size, validation setting (e.g., OR, cadaver laboratory), assessment process (e.g., direct observation, recordings), and type of assessor(s).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations